Validation test on 3d heart phantom for mitral valve leaflet tracking - Lina Farhana Mahadi; Nabilah Ibrahim; Shahnoor Shanta; Hideyuki Hasegawa (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Mitral valve movement is essential to be identified in order to monitor the abnormality of blood flow in right side of heart. The estimation and tracking of mitral valve has seldom been investigated since it required high temporal rate to scan the echocardiography images and it depends on the operator to capture the low-speckle and-noise images. This study presents the validation experiment performed on heart phantom made of thermoplastic polyurethane (TPU) filament which the objective is to validate the previous features tracking technique implemented in mitral valve locating in video frames using Kanade-Lucas-Tomasi (KLT) algorithm. The outcome was able to automatically detect the edge of mitral valve and thus in future, it manages to predict the flowing of blood pattern. An in-vitro experiment was conducted which involved a valve phantom scanning in water tank that connected to water pump. It was found in this study that the technique capable to detect and visualize the mitral valve up to 59 frames in 2.36 secondsby tracking the features of minimum eigenvalue within the selected region. It was also produced a good agreement of valve distance between the true value and the measured one, which achieved the minimum of 88% similarity. This yielded the validation of the proposed technique to track and visualize the mitral valves.